2018
DOI: 10.1097/rlu.0000000000001943
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Recurrent/Residual Glioma From Radiation Necrosis Using Semi Quantitative 99mTc MDM (Bis-Methionine-DTPA) Brain SPECT/CT and Dynamic Susceptibility Contrast-Enhanced MR Perfusion

Abstract: Thus, combining MDM SPECT with DSCE MRI may provide an accurate method for differentiation of tumor recurrence from radiation-induced necrosis in glioma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In a meta-analysis that evaluated the diagnostic ability of SPECT in differentiating glioma recurrence from radiation necrosis, the pooled sensitivity was 89% and the specificity 88% [58]. Other promising tracers for SPECT to differentiate tumor recurrence from radiation necrosis include pentavalent technetium-99m dimercaptosuccinic acid (Tc-99m (V) DMSA) [59], bis-methionine-DTPA (Tc MDM) [60], and 99m-technetium glucoheptonate ( 99m Tc-GHA) [61].…”
Section: Diagnostic Imaging Modalitiesmentioning
confidence: 99%
“…In a meta-analysis that evaluated the diagnostic ability of SPECT in differentiating glioma recurrence from radiation necrosis, the pooled sensitivity was 89% and the specificity 88% [58]. Other promising tracers for SPECT to differentiate tumor recurrence from radiation necrosis include pentavalent technetium-99m dimercaptosuccinic acid (Tc-99m (V) DMSA) [59], bis-methionine-DTPA (Tc MDM) [60], and 99m-technetium glucoheptonate ( 99m Tc-GHA) [61].…”
Section: Diagnostic Imaging Modalitiesmentioning
confidence: 99%
“…Generally, in traditional nuclear medicine imaging, single photon emission computed tomography (SPECT) modality has been used for qualitative diagnosis by visual evaluation of radioactive distribution. For quantitative analysis, the target/nontarget (T/NT) ratio calculated from counts of their regions of interest (ROI) was widely used in SPECT modality, which was known as the semiquantitative analysis [1, 2]. Positron emission tomography (PET) was regarded as the only modality capable of absolute quantitative analysis in the past [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, these high-dimensional features were reduced by a stepwise forward feature selection scheme that reduces each of the initial feature sets to only 25 different features through the gain equation (2). Third, the dataset used in this study was relatively small, which was also the problem identified in previous studies [1, 3842]. Therefore, a large patient cohort was necessary to create a more robust model.…”
Section: Discussionmentioning
confidence: 96%
“…Gliomas are the most common and aggressive brain tumors in adults and have an approximate 5-year survival rate of 10% in their highest grade (e.g., glioblastoma multiforme) [1]. The conventional therapy for gliomas is surgery followed by conventional radiotherapy/chemotherapy [1, 2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation